Fabrication of a zeolite imidazole framework-8-based red emitting nanocomposite for sensitive detection of nitro reductase. (June 2022) - Wu, Jichun; Zhai, Jia; Wang, Binbin; Ding, Wenjing; Ding, Rui; Li, Ke; Muhammad, Sohail; Zhang, Xing; He, Peng; Shen, Baoxing
Abstract: Hypoxia is one of the common characteristics in tumor cells. It has been confirmed that the nitro reductase (NTR) overexpression is closely related to hypoxia cells. Thus, developing a facile method to detect nitro reductase is of great significance. Although several detection techniques have been designed for the NTR, these probes still have limitations, such as low sensitivity, poor water solubility, and compromised biocompatibility. In this study, we developed a nanocomposite (Nitro-BOD@ZIF-8) based on BODIPY fluorophore and zeolitic imidazolate framework-8 (ZIF-8). A red emission BODIPY small molecule probe (Nitro-BOD) was synthesized and then encapsulated in ZIF-8. Morpholine and nitro groups were introduced to Nitro-BOD for lysosome localization and NTR detection, respectively. The results showed that reduction of the nitro group on the probe by NTR blocked the photoinduced electron transfer (PET), resulting in fluorescence enhancement. The low detection limit for the NTR proved the sensitivity of the sensor. In addition, confocal microscopy con-firmed the fluorescence imaging feature of the Nitro-BOD@ZIF-8 for NTR in A549 cells. This work also opens a useful path for probe and MOF in the field of enzyme detection. Graphical abstract: Image 1 Highlights: Nitro-BOD based on PET, encapsulated with ZIF-8, opening the way for MOFs material in enzyme-reaction probes. Nitro-BOD can be applied to lysosome localization as well as NTR detection in A549 cells. Binding point between imidazole and amino helps to improve the fluorescence response significantly.